2023
DOI: 10.3389/fmicb.2023.1179966
|View full text |Cite
|
Sign up to set email alerts
|

Oxford nanopore long-read sequencing enables the generation of complete bacterial and plasmid genomes without short-read sequencing

Abstract: IntroductionGenome-based analysis is crucial in monitoring antibiotic-resistant bacteria (ARB)and antibiotic-resistance genes (ARGs). Short-read sequencing is typically used to obtain incomplete draft genomes, while long-read sequencing can obtain genomes of multidrug resistance (MDR) plasmids and track the transmission of plasmid-borne antimicrobial resistance genes in bacteria. However, long-read sequencing suffers from low-accuracy base calling, and short-read sequencing is often required to improve genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…We investigated the difference in read quality metrics between RBKv10, RBKv14, and LSKv14 library preparation kits, and found that read Q-scores were highest with LSKv14 followed by RBKv14, but read length distribution was best with RBKv14. Both LSKv14 and RBKv14 had better read quality metrics than RBKv10, which agree with other studies 6,11,17,18 . While LSKv14 had higher Q-scores, the read length distribution for RBKv14 had a better representation of longer reads in the RBKv14 datasets, whereas the LSKv14 read size was skewed towards shorter reads, which has been observed previously with older kit/flowcell versions (SQK-LSK108 & SQK-RAD002 on R9.4.1 flow cells) 12,13 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We investigated the difference in read quality metrics between RBKv10, RBKv14, and LSKv14 library preparation kits, and found that read Q-scores were highest with LSKv14 followed by RBKv14, but read length distribution was best with RBKv14. Both LSKv14 and RBKv14 had better read quality metrics than RBKv10, which agree with other studies 6,11,17,18 . While LSKv14 had higher Q-scores, the read length distribution for RBKv14 had a better representation of longer reads in the RBKv14 datasets, whereas the LSKv14 read size was skewed towards shorter reads, which has been observed previously with older kit/flowcell versions (SQK-LSK108 & SQK-RAD002 on R9.4.1 flow cells) 12,13 .…”
Section: Discussionsupporting
confidence: 91%
“…Genome contiguity becomes important when considering the mechanisms and drivers of antimicrobial resistance in bacterial pathogens. Plasmids are common vectors for horizontal gene transfer, and obtaining complete plasmid sequences is the most effective means to detect the coexistence of antimicrobial resistance genes on the same plasmid 6 , as well as the potential for that plasmid to transfer to other strains, species, or genera 7 . Long-read sequencing is usually essential to discern complete plasmid structures 6 , which often contain repetitive sequences that are difficult to resolve with short-read sequencing data alone 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly 80 Xt genomes are publicly available, and many of these have been assembled using longread sequencing, including PacBio and Oxford Nanopore Technology (ONT), which may or may not be corrected with short-read sequencing such as Illumina [10][11][12]. While long-read sequencing is useful in detecting large polymorphisms or structural variation, the base sequence accuracy is lower than with short-read sequencing [13].…”
Section: Introductionmentioning
confidence: 99%